1995
DOI: 10.1152/ajpheart.1995.269.2.h609
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical determinants of myocardial oxygen consumption in conscious dogs

Abstract: A new practical descriptor of metabolic to mechanical myocardial energy transfer (MET), termed the virtual work model, was evaluated in 32 conscious dogs and in 8 isolated canine hearts. An index of total mechanical energy expenditure (TME) was calculated as the sum of external energy (stroke work) and an internal energy index of heat (left ventricular end-diastolic volume times left ventricular mean ejection pressure). Physiological comparison of TME (x-axis) and myocardial oxygen consumption (MVO2; y-axis) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Thus Vanoverschelde [138] has reported a mean VO 2 of 5 ml O 2 100 g Ϫ1 min Ϫ1 (ϳ17 mW g Ϫ1 ) compared with the expected textbook values for man of 26-33 mW g Ϫ1 . In conscious dogs in vivo, Elbeery et al [139] reported a low value (17 mW g Ϫ1 ), but found a mean value of 36 mW g Ϫ1 in isolated hearts studied in parallel. Part of the reason for the lower VO 2 values relates to the lower heart rates and lower end-diastolic volumes in the conscious animals.…”
Section: Basal Metabolism Mechanical Efficiency and Species Difmentioning
confidence: 96%
“…Thus Vanoverschelde [138] has reported a mean VO 2 of 5 ml O 2 100 g Ϫ1 min Ϫ1 (ϳ17 mW g Ϫ1 ) compared with the expected textbook values for man of 26-33 mW g Ϫ1 . In conscious dogs in vivo, Elbeery et al [139] reported a low value (17 mW g Ϫ1 ), but found a mean value of 36 mW g Ϫ1 in isolated hearts studied in parallel. Part of the reason for the lower VO 2 values relates to the lower heart rates and lower end-diastolic volumes in the conscious animals.…”
Section: Basal Metabolism Mechanical Efficiency and Species Difmentioning
confidence: 96%
“…First, whether an oxygen-wasting effect is truly an effect of inotropic drugs is uncertain because it can be partly explained by the particular mechanical index used for the assessment. An energetic cost can be calculated without excessive oxygen consumption by using, for instance, the pressure-work index proposed by Rooke and Feigl 14 or the total mechanical energy (TME) model developed by Elbeery et al 15 Second, most of these studies have been conducted in isolated hearts and not in vivo. Therefore, this phenomenon could, in large part, be restricted to the isolated-heart models.…”
Section: Clinical Perspective On P 285mentioning
confidence: 99%
“…Therefore, this phenomenon could, in large part, be restricted to the isolated-heart models. 15 Finally, the doses of inotropes needed to show such a wasting of oxygen in vivo have been excessive, inducing profound tachycardia and blood pressures exceeding clinical goals. 16,17 In this study, we investigated whether the inotropic drugs dobutamine and levosimendan have relatively increased oxygen consumption (oxygen wasting) in clinically relevant doses applied in a large-animal model of postischemically reduced left ventricular function.…”
Section: Clinical Perspective On P 285mentioning
confidence: 99%
See 2 more Smart Citations